2022
DOI: 10.1007/s13158-022-00324-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of FOCUS App for Assessment of Approaches to Learning in 3–8-Year-Old Children in Kenya: A Design-Based Research Approach

Abstract: Performance-based tools to assess school readiness domains such as Approaches to Learning are lacking in Low and Middle-Income Countries such as Kenya. This study aims to develop the Kenyan version of the FOCUS app (Finding Out Children's Unique Strengths), a game-like computer tablet assessment of two Approaches to Learning domains: mastery motivation and executive functions. We used a design-based research approach to develop and validate the FOCUS app, initially designed for the US and Hungarian Cultures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…However, when adopted in Indonesia, linguistic inconsistency problems have resulted in misunderstandings for students. Research in various countries has shown the validity and reliability of Holland's instrument, but cultural contextual factors may affect its applicability (Amukune et al, 2023;Fekih-Romdhane et al, 2023). This study aims to re-measure the validity and reliability of Holland's career interest instrument in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, when adopted in Indonesia, linguistic inconsistency problems have resulted in misunderstandings for students. Research in various countries has shown the validity and reliability of Holland's instrument, but cultural contextual factors may affect its applicability (Amukune et al, 2023;Fekih-Romdhane et al, 2023). This study aims to re-measure the validity and reliability of Holland's career interest instrument in Indonesia.…”
Section: Introductionmentioning
confidence: 99%